Athletic biomechanical system trajectory modeling experiment using body mass and length - Zagrevskiy, V. I.; Zagrevskiy, O. I. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to offer and substantiate by computation experiments basics of the athletic biomechanical system trajectory modeling using the mass-inertial characteristics and elementary kinematics of the body parts.